A novel combined anodic-adhesive bonding technique for joining glass to metal for micro device applications. (September 2022) - Nazari, Roohollah; Khoramishad, Hadi
Abstract: In this study, a novel bonding technique consisting of anodic and adhesive bonding methods was proposed for joining glass to metal. The Pyrex glass substrate was metallized with a thin aluminum foil using anodic bonding and then it was bonded to a thick aluminum substrate by adhesive bonding using an epoxy adhesive. The effect of metallization and different surface treatments was examined on the bonding surface characteristics and joint strength by measuring the surface morphology, roughness and contact angle and mechanical testing single lap joints. The results showed that metallizing and abrading glass surfaces both improved the bonding surface wettability and joint strength. Abrading the glass bonding surface of the glass-aluminum joint caused the joint strength to improve by 20%, while metallizing and abrading glass bonding surface resulted in a synergistic effect on the joint strength with a 75% improvement. Furthermore, the failure mode of the joints was considerably influenced by the surface metallization and treatment methods.